Finding Meaning in Financial Sustainability; an empirical analysis of ESG ratings and performance - Brown, Jacqueline D. (Tufts Archival Research Center, 2023)
This paper analyzes the correlation between environmental, social, governance ratings and financial performance for mutual funds. It then compares how the correlation differs when analyzing funds based in the EU vs. the U.S. The paper describes the ESG policies in place in both the EU and the U.S., as well as a section on how ESG ratings are calculated, followed by the methodology section which includes the regression model and results found. Ultimately, results were ambiguous and depended on the financial metric analyzed, but showed a general trend where higher ESG ratings did not necessarily correlate to higher financial performance.; Thesis (B.A.)--Tufts University, 2023.; Submitted to the Dept. of Economics.; Advisor: Ujjayant Chakravorty.